2019
DOI: 10.1080/14786419.2019.1585844
|View full text |Cite
|
Sign up to set email alerts
|

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities

Abstract: A new phenanthropyran, dioscorone B (1), and a new phenanthrene (2), together with seven known compounds (3-9), were isolated from the 75% ethanol extract of Dioscorea septemloba rhizomes. The chemical structures of these compounds were elucidated by comprehensive spectroscopic methods including NMR, HRESIMS, IR, and UV spectra. Compounds 1-5 were first isolated from genus Dioscorea. The proton and carbon chemical shifts of compounds 1-9 were unambiguously assigned based on the 1D-NMR and 2D-NMR data. Compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition, the authors determined that the levels of allantoin, adenosine, and glutamine increased with the growing years. 2,7-Dihydroxy-4,6-dimethoxy phenanthrene, 6,7-dihydroxy-2,4-dimethoxy phenanthrene and 6-hydroxy-2,4,7-trimethoxyphenanthrene (batatasin I) were identified in the EtOH extracts of yam tuber (D. batatas) peel, while in the flesh, they were not detected; these phenanthrene derivatives scavenged DPPH -scavenging activities, with IC 50 values of 0.07 ± 0.10 µM and 0.13 ± 0.09 µM, respectively [172]. Using UPLC-DAD-Q-TOF-MS/MS, Zhao et al [29] detected 42 and 38 compounds in methanol extracts of D. oppositifolia (Chinese yam) and D. hamiltonii, respectively, while 14 of them were quantified using HPLC.…”
Section: Phytochemicals Of Dioscoreamentioning
confidence: 99%
“…In addition, the authors determined that the levels of allantoin, adenosine, and glutamine increased with the growing years. 2,7-Dihydroxy-4,6-dimethoxy phenanthrene, 6,7-dihydroxy-2,4-dimethoxy phenanthrene and 6-hydroxy-2,4,7-trimethoxyphenanthrene (batatasin I) were identified in the EtOH extracts of yam tuber (D. batatas) peel, while in the flesh, they were not detected; these phenanthrene derivatives scavenged DPPH -scavenging activities, with IC 50 values of 0.07 ± 0.10 µM and 0.13 ± 0.09 µM, respectively [172]. Using UPLC-DAD-Q-TOF-MS/MS, Zhao et al [29] detected 42 and 38 compounds in methanol extracts of D. oppositifolia (Chinese yam) and D. hamiltonii, respectively, while 14 of them were quantified using HPLC.…”
Section: Phytochemicals Of Dioscoreamentioning
confidence: 99%
“…This herb medicine is mainly planted in Zhejiang, Fujian, and Jiangxi Provinces, China, which has been famous for its application of the treatments of gonorrhea white turbid, excessive leucorrhea, damp heat sore poison, waist and knee arthralgia, and so on [2][3][4][5][6]. Chemical studies of D. spongiosa have indicated the main chemical constituents as steroids, triterpenoid saponins, diarylheptanes, flavonoids, and lignans, with the first two kinds being the major ones [7][8][9][10], which showed various pharmacological activities including lowering uric acid, anti-diabetic, anti-inflammation, anti-tumor, anti-atherosclerosis, regulating blood lipids, anti-oxidation, antibacterial [11]. Commonly, active compounds were usually obtained firstly by chromatographic techniques including silica gel column chromatography, macroporous resin column chromatography (MRCC), high-pressure preparative column chromatography, and preparative high-performance liquid chromatography, and then subjected to the activity assays by pharmacological tests.…”
Section: Introductionmentioning
confidence: 99%
“…1), diosniponol C (3), montroumarin(7), dioscorone A(8), diosniponol D(9), and one phenanthropyran compound, dioscorone A (8) were successfully separated. Finally, the isolates were assayed for their urico-lowering activities, anti-inflammatory activities, and hypoglycemic activities in vitro, compounds 2, 4, 5, 6, 10, 11, and 12 showing significant anti-inflammatory activities, with compounds 3, 5, 6, 11, and 12 showing significant urico-lowering activities, with compound 2, 4, 5, 6, 10, and 11 showing significant hypoglycemic activities, which indicated that the steroidal saponins of 5, 6, and 11 showed all these three activities, suggesting the steroidal saponins as the main active components in D. spongiosa.…”
mentioning
confidence: 99%